On a Subclass of Meromorphic Multivalent Functions - Atshan, Waggas Galib; HadiAbd, Enaam (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
In this paper, we introduce a new class of meromorphic multivalent functions in the puncturedunit discU*zâˆˆc:0 <|z|<1 . We obtain various resultsincluding coefficients inequality, convex set, radius of starlikeness and convexity, Î´-neighborhoods , arithmetic mean and extreme points .